Quarter notes and bank notes : the economics of music composition in the eighteenth and nineteenth centuries - Scherer, F. M. (Frederic M.) (Princeton economic history of the Western world., 2004)
"F. M. Scherer examines the political, intellectual, and economic roots of the shift from patronage to a freelance market. He describes the eighteenth-century cultural "arms race" among noble courts, the spread of private concert halls and opera houses, the increasing attendance of middle-class music lovers, and the founding of conservatories. He analyzes changing trends in how composers acquired their skills and earned their living, examining such factors as demographic developments and new modes of transportation.